Legal Politics of Formation and Empowerment of Village-Owned Enterprises in the Perspective of the Village Law to Realize Community Welfare and Independence - Harmono Harmono (Cita Konsultindo Research Center, 2023)
One of the objectives of establishing the Unitary State of the Republic of Indonesia as stated in the preamble to the 1945 Constitution is to realize the welfare of the community. To realize this goal in the village community, efforts are made both through the making of laws and regulations and social programs. The efforts made are the opening of opportunities for villages to have business entities whose capital can be taken from village funds, namely Village-Owned Enterprises (BUMDes) in the period 2005 to 2020, there are 51,134 villages that already have BUMDes with village funds disbursed around Rp. 4.2 trillion. This study aims to analyze and find matters related to the government's legal politics and formulate strategies in order to improve community welfare through Village-Owned Enterprises ( BUMDes. The method in this study uses a qualitative approach with a descriptive type of writing. The selected data is the generalpublic as informants and managers of selected BUMDes as samples, data analysis using data production steps, data presentation and drawing conclusions.The results showed that the establishment of Village-Owned Enterprises (BUMDes) has not been able to significantly realize the welfare of rural communities. This is due in addition to the low resources of the village community, especially the village elites in interpreting the government's legal political objectives regarding Village Miilik Business Entities, as well as the lack of assistance in the formation and empowerment of Village-Owned Enterprises. Itcan be said that there are still weaknesses in the legal system as well asthe lack of thinking ability and lack of legal awareness of stakeholders. BUMDes contribute to economic independence and one BUMDes in relation to aspects of compliance with laws and regulations have implications for the ability to manage village potential.